2011
DOI: 10.1249/mss.0b013e3181fcee7d
|View full text |Cite
|
Sign up to set email alerts
|

Creatine in Type 2 Diabetes

Abstract: Creatine supplementation combined with an exercise program improves glycemic control in type 2 diabetic patients. The underlying mechanism seems to be related to an increase in GLUT-4 recruitment to the sarcolemma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 28 publications
1
51
0
Order By: Relevance
“…Moreover, we reported that 3 months of creatine supplementation had no deleterious effect on kidney function in post-menopausal women [9] and in type-2 diabetic patients [17], corroborating the safety of this supplement. The present data extend this notion to typical creatine consumers, suggesting that healthy resistance-trained individuals can “deal” with creatine supplementation even in combination with a higher level of protein intake (considering the Recommended Dietary Intake (RDI) of 0.8 g/Kg/d).…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, we reported that 3 months of creatine supplementation had no deleterious effect on kidney function in post-menopausal women [9] and in type-2 diabetic patients [17], corroborating the safety of this supplement. The present data extend this notion to typical creatine consumers, suggesting that healthy resistance-trained individuals can “deal” with creatine supplementation even in combination with a higher level of protein intake (considering the Recommended Dietary Intake (RDI) of 0.8 g/Kg/d).…”
Section: Discussionmentioning
confidence: 66%
“…Type 1 diabetic patients under poor glycemic control, common in low income or un-insured patients in the United States or in under-developed countries (67) exhibit detrimentally low intracellular energy metabolism and significant weight loss, leading to chronic fatigue and general body weakness. l -Cit may protect against diabetic muscle wasting via nutritional support, providing the precursor for creatine synthesis (68, 69). …”
Section: Discussionmentioning
confidence: 99%
“…They were asked to dissolve the supplements preferably in juice, in order to mask the supplements. The compliance to creatine supplementation was monitored weekly by personal communication, as previously done in our studies in which creatine supplementation was shown to be capable of increasing muscle phosphorylcreatine content [26-28]. The supplement packages were coded, so that, neither the investigators nor the participants were aware of the contents until completion of the analyses.…”
Section: Methodsmentioning
confidence: 99%